Association of Lifestyle and Food Consumption with Bone Mineral Density among People Aged 50 Years and Above Attending the Hospitals of Kathmandu, Nepal. (22nd May 2019) - Chaudhary, Narendra Kumar; Timilsena, Mukti Nath; Sunuwar, Dev Ram; Pradhan, Pranil Man Singh; Sangroula, Raj Kumar
Abstract : Background . Bone mineral density (BMD) is the measure of the minerals, mostly calcium and phosphorous, contained in certain volume of bone to diagnose osteoporosis. The aim of the study was to find out the association of lifestyle and food consumption with BMD. Methods . An analytical cross-sectional study was conducted among 169 people of age 50 years and above who underwent Dual Energy X-Ray Absorptiometry (DEXA or DXA) scan in the hospitals of Kathmandu valley of Nepal. Food frequency questionnaire and 24-hour recall methods were followed. The DXA reports of the participants were observed to identify osteoporosis. Chi-square test, independent sample t-test, and binary logistic regression were applied to explore the association of BMD with different variables. Result . The prevalence of osteoporosis, osteopenia, and normal BMD was 37.3%, 38.5%, and 24.2%, respectively. The prevalence of osteoporosis increased with sex and age (AOR 3.339, CI: 1.240-8.995, p-value 0.017; AOR 3.756, CI: 1.745-8.085, p-value 0.001), respectively. Higher BMI was associated with lower odds of osteoporosis (AOR 0.428, CI: 0.209-0.877, p-value 0.020). Smoking had bad effect on the health of bone (AOR 3.848, CI: 1.179-12.558, p-value 0.026). Daily dietary calcium intake had negative association with osteoporosis with the p-value of 0.003; however, the daily consumption of vitamin D rich food had no association with osteoporosis. Conclusion . High prevalence of osteoporosis and osteopenia was found in older people. Osteoporosis was found to be significantly associated with sex, age, lower BMI, smoking habit, and daily calcium consumption. Further research can be conducted by making the relationship of calcium consumption with the numerical T-value of scanned body parts.